Comparing the antidiabetic effects and chemical profiles of raw and fermented Chinese Ge-Gen-Qin-Lian decoction by integrating untargeted metabolomics and targeted analysis - Yan Yan; Chenhui Du; Zhenyu Li; Min Zhang; Jin Li; Jinping Jia; Aiping Li; Xuemei Qin; Qiang Song (BMC, 2018)
Abstract Background Microbial fermentation has been widely applied in traditional Chinese medicine (TCM) for thousands of years in China. Various beneficial effects of fermentation for applications in TCM or herbals have been reported, such as enhanced anti-ovarian cancer, antioxidative activity, and neuroprotective effects. Ge-Gen-Qin-Lian decoction (GQD), a classic TCM formula, has been used to treat type 2 diabetes mellitus in China. In this study, GQD was fermented with Saccharomyces cerevisiae, and the antidiabetic activities and overall chemical profiles of raw and fermented GQD (FGQD) were systematically compared. Methods First, the antidiabetic effects of GQD and FGQD on high-fat diet and streptozotocin (STZ)-induced diabetic rats were compared. Then, high-performance liquid chromatography Q Exactive MS was applied for rapid characterization of the chemical components of GQD. Additionally, we proposed an integrated chromatographic technique based untargeted metabolomics identifying differential chemical markers between GQD and FGQD and targeted analysis determining the fermenting-induced quantitative variation tendencies of chemical marker strategy for overall chemical profiling of raw and fermented GQD. Results Both GQD and FGQD displayed effects against HFD and STZ-induced diabetes, and FGQD showed a better recovery trend associated with profound changes in the serum lipoprotein profile and body weight gain. In addition, 133 compounds were characterized from GQD. It was demonstrated that the integrated strategy holistically illuminated 30 chemical markers contributed to the separation of GQD and FGQD, and further elucidated the fermenting-induced chemical transformation mechanisms and inherent chemical connections of secondary metabolites. Although there were no new secondary metabolites in FGQD compared with GQD, the amounts of secondary metabolites, which were mostly deglycosylated, were redistributed in FGQD. Conclusion The anti-diabetic activities of GQD could be improved by applying fermentation technology. Moreover, the proposed strategy could serve as a powerful tool for systematically exploring the chemical profiles of raw and fermented formulas.